Immune biomarkers and anti‐HIV activity in the reproductive tract of sexually active and sexually inactive adolescent girls. (13th March 2018) - Ghosh, Mimi; Jais, Mariel; Biswas, Roshni; Jarin, Jason; Daniels, Jason; Joy, Christopher; Juzumaite, Monika; Emmanuel, Vanessa; Gomez‐Lobo, Veronica
Abstract : Problem: Adolescent girls are disproportionately affected by the HIV/AIDS pandemic, accounting for 22% of all new HIV infections globally. Yet little is known regarding the immune microenvironment of the adolescent female reproductive tract, especially regarding differences among sexually active and inactive girls, a critical parameter to evaluate HIV susceptibility associated with young age and sexual debut. Methods: Cervico‐vaginal lavage (CVL) was collected from sexually active (10) and inactive (8) girls aged 11‐19 years and analyzed by ELISA for inflammation‐associated biomarkers IL‐6, IL‐8, TNF‐α, MIP‐3α, IL‐1α, IL‐1β, matrix metalloproteinases (MMP) 1, 2, 7, 8, and 9, as well as anti‐HIV mediators, Elafin, SLPI, human beta‐defensin 2, and tissue inhibitor of matrix metalloproteinases (TIMP) 1 and 2. Cervical ectopy was analyzed using Volocity. Anti‐HIV activity was determined by TZM‐bl assay. Statistical analyses were performed using GraphPad Prism and R. Results: Sexually inactive girls had significantly higher levels of TNF‐α ( P  = .029) in CVL compared to sexually active girls. In contrast, sexually active girls showed a trend toward higher levels of IL‐1α ( P  = .051) compared to the sexually inactive girls. Heat‐map correlations between cervical ectopy and immune biomarkers were also distinct between the 2 populations with significant positive associations between % ectopy and inflammation‐associated biomarkers IL‐6, IL‐1β, IL‐8, MIP‐3α, MMP‐8, and MMP‐9 observed in the sexually inactive but not sexually active group. Conclusion: Higher pro‐inflammatory biomarker TNF‐α, as well as a distinct inflammation‐associated immune clustering in sexually inactive girls, can potentially increase risk for infections including HIV upon sexual debut. Future studies with larger sample sizes are needed to characterize the immune parameters associated with sexual activity.